Prediction of Financial Behavior with Financial Literacy as a Moderating Variable in Muhammadiyah Religious Organizations in Indonesia: Prediksi Financial Behaviour Dengan Literasi Keuangan sebagai Variabel Moderasi pada Organisasi Keagamaan Muhammadiyah di Indonesia - Lailiyah, Elliv Hidayatul; Dewi, Arfiana; Shidiq, Yahya; Lestari, Dian (Journal of Accounting Science, 2022)
The COVID-19 pandemic has an impact on all aspects of life, including the financial condition of each individual. People who do not have good financial literacy will have more complex financial problems. Members of the Muhammadiyah organization are also affected by this pandemic. The purpose of this study is to determine the prediction of Financial Behavior and to determine the role of financial literacy moderation in Muhammadiyah Organizations in Indonesia. This study tested 102 members of the organization using Convenience sampling method, data analysis using Moderated Regression Analysis (MRA). The results showed that Locus of Control, Financial Attitude, Income, and Religiosity succeeded in predicting Financial Behavior and financial literacy managed to moderate the effect on these variables. The results of the study have implications that members of the Muhammadiyah organization in Indonesia have good financial behavior based on the research variables used in this study.